Homegardens and woman’s work in peri-urban space: a case study in Santarém, Pará, Brazil (Research, Society and Development, 2020)
Family agriculture contributes significantly to food production and income generation in the Amazonia. This study aimed to examine the socioeconomic contribution of agroforestry homegardens production managed by women in peri-urban space on the banks of Lake of Maicá, Santarém, Brazil. This case study was carried out with female farmers associated with the Union of Rural Workers. Women generates income and produces food that guarantee food and nutritional security for them and their families; raise animals and grow vegetables and fruit. Agroforestry homegardens are production spaces organized by women and perform social, environmental, cultural and economic functions.